2019
DOI: 10.1186/s41935-019-0158-y
|View full text |Cite
|
Sign up to set email alerts
|

Chrysomya megacephala (Fabricius, 1794) (Diptera: Calliphoridae) development by landmark-based geometric morphometrics of cephalopharyngeal skeleton: a preliminary assessment for forensic entomology application

Abstract: Background: Considering the practicality of geometric morphometrics which could discriminate insect species, this application was extended to the analysis of blow fly larval growth based on cephalopharyngeal skeleton. In forensic entomology, cephalopharyngeal skeleton plays a crucial role in species identification but the morphometric information of this part is scarce. In this study, Chrysomya megacephala (Fabricius, 1794) was reared in two study replicates in natural conditions and samplings were conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…However, typically, they do not drastically differ between instars within a species, which makes quantitative measures of maturity necessary. The shape or colour of a feature can be quantitatively described by morphometrics [ 33 , 34 ] or spectrometry, respectively. Pupal development does not progress through discrete stages, but the development of certain features (such as seta formation or setal pigmentation) can be treated as discrete developmental landmarks at sufficiently coarse time scales and continuous developmental processes at finer temporal resolutions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, typically, they do not drastically differ between instars within a species, which makes quantitative measures of maturity necessary. The shape or colour of a feature can be quantitatively described by morphometrics [ 33 , 34 ] or spectrometry, respectively. Pupal development does not progress through discrete stages, but the development of certain features (such as seta formation or setal pigmentation) can be treated as discrete developmental landmarks at sufficiently coarse time scales and continuous developmental processes at finer temporal resolutions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work on the application of geometric morphometrics to wing shape analysis of species from the Sarcophagidae and the Calliphoridae family showed that wing shape variation was reliable for classifying Chrysomya species [37] and even distinguishing between sexes of the same species [38]. Further application to cephalopharyngeal skeleton shape of fly larvae is also possible [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Studying the efficacy of the cephalopharyngeal skeleton as a growth parameter is therefore necessary as in the later studies recorded it grew proportionally with larval body size during active feeding stage (Eliza & Zuha, 2018;Sim & Zuha, 2019). The current study compared the effect of hot water and direct killing by immersion in 70% ethanol on the cephalopharyngeal skeleton and total body size of third instar Chrysomya megacephala (Fabricius, 1786) larvae, a forensically important blowfly in Malaysia, Thailand, and the rest of the world (Lee et al, 2004;Sukontason et al, 2008;Thevan et al, 2010;Badenhorst & Villet, 2018).…”
mentioning
confidence: 99%
“…The internal tissues surrounding the cephalopharyngeal skeleton were carefully removed in 10% KOH and subsequently transferred into 10% acetic acid for 10 min. Cephalopharyngeal skeleton was then soaked in 70% ethanol for 20 min before they were mounted onto a glass slide in lateral position using Berlese fluid and covered by a 6 mm round coverslip (Sim & Zuha, 2019). Measurements of the cephalopharyngeal skeleton were conducted immediately after the mounting process based on inter landmark distances between anterodorsal process (tip of the dorsal bridge) to dorsal cornu (ADP-DC), the anterodorsal process to ventral cornu (ADP-VC), and dorsal cornu to ventral cornu (DC-VC) (Nateeworanart et al, 2010;Nuñez & Liria, 2016;Rabbani & Zuha, 2017) (Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation